Organizational Behavior - Abhishek Chakraborty; Tulika Chakraborty; T. Jayant Naidu (Behavioural Perspectives, 2021)
Organizational behavior is the study of human behavior in the place of work, the relations between people and the organization with the aim to know and forecast human behavior. The accepting of person, group, and organizational behavior is important to accomplishment as a leader or an admirer, and it necessitate a methodical lesson to even begin to grasp all of the variables that impact behavior. For being a good manager requires well-built interpersonal skills, as communication is vital, one ought to manage different types of resources: people, money, and time in order to achieve specific goals.